Vladimir Ilyich Lenin. A short biography. [By V. Zevin and G. Golikov.] Transl. from the Russian (Novosti Press Agency Publishing House, 1972)
Original title: Vladimir Il'ič Lenin. Kratkij biografičeskij očerk.